Computational fluid dynamics modelling and experimental analysis of a Photovoltaic Thermal system with spiral absorber using hybrid TiO2 – MWCNT nanofluid. Issue 1 (May 2021) - Sacithra, A.; Gomathi, S.; Manivannan, A.
Abstract: The temperature increase of the PV panel reduces the electrical efficiency of the module. In order to boost electrical efficiency, the temperature of the PV panel is decreased by working fluids such as water and water based TiO2 -MWCNT hybrid nanofluid. The pattern of the absorber is spiral. The spiral flow absorber collector is a steady loop. This model was implemented to determine the total heat gain and total combined efficiency of the PV module. The findings show that total thermal performance, optimum thermal output and electrical performance achieved by TiO2 –MWCNT nanofluid is more compared with water. In the nanofluid coefficient of convective heat transfer is higher than that of the base liquid at the same mass flow rate. For a mass flow rate of 0.01 kg/sec, the maximum thermal efficiency and electrical efficiency obtained are 52.8 per cent and 8.6 per cent, respectively, relative to the simulation results.